On the Acoustics of Policy Learning: Can Co‐Participation in Policy Forums Break Up Echo Chambers?. Issue 2 (12th December 2019) - Malkamäki, Arttu; Wagner, Paul M.; Brockhaus, Maria; Toppinen, Anne; Ylä‐Anttila, Tuomas
Abstract : Overcoming common‐pool resource dilemmas requires learning across different sectors of society. However, policy actors frequently entrench themselves in so‐called echo chambers by preferring to rely on information from those whose policy beliefs resemble their own. Policy forums can reduce the limiting effects of echo chambers by encouraging actors with diverse knowledge bases to exchange information and learn from one another. This paper applies exponential random graph models to network data from the South African tree plantation policy domain to investigate how belief homophily, reputational influence, and forum co‐participation shape information exchange behavior. Results show that echo chambers are important determinants of information exchange ties and that reputational influence is likely to "deepen" the echo. Results also show that the more forums that a pair of actors co‐participate in, the more likely they are to exchange information. This applies to information exchange generally, as well as information exchange with trusted partners. Findings indicate that forums enable both cognitive learning (as knowledge gains) and relational learning (as improved relations). Nonetheless, when echo chambers are strong, and many forums are polarized, then forum co‐participation may not break up echo chambers. Abstract : 克服"共有资源"（common‐pool resource）困境需要不同社会部门之间的学习。然而，政策行为者时常通过偏好依赖政策信念与其相似的人士所提供的信息，而将自身置于所谓的回音室。政策论坛能通过鼓励拥有不同知识储备的行动者进行信息交流和相互学习，进而减少回音室产生的限制性效果。本文对南非林业政策领域的网络数据应用指数随机图模型，以调查信念同质性、声望影响、论坛共同参与如何影响信息交换行为。调查结果显示，回音室是信息交换关系的重要决定因素，并且声望影响很有可能"加深"回音室（的影响）。研究结果还显示，一对行动者共同参与的政策论坛越多，他们就越有可能交换信息。这一般适用于信息交换，以及相互信任的伙伴之间的信息交流。研究结果显示，论坛使认知学习（作为增加知识）和关系学习（作为改善关系）成为可能。尽管如此，当回音室存在强有力影响，并且许多论坛出现极化现象时，论坛共同参与可能无法打破回音室。 Abstract : Superar los dilemas de recursos comunes requiere aprender en diferentes sectores de la sociedad. Sin embargo, los actores políticos con frecuencia se atrincheran en las llamadas cámaras de eco al preferir confiar en la información de aquellos cuyas creencias políticas se parecen a las suyas. Los foros de políticas pueden reducir los efectos limitantes de las cámaras de eco al alentar a los actores con diversas bases de conocimiento a intercambiar información y aprender unos de otros. Este documento aplica modelos de gráficos aleatorios exponenciales a los datos de la red del dominio de la política de plantación de árboles de Sudáfrica para investigar cómo la homofilia, la influencia de la reputación y la coparticipación en el foro configuran el comportamiento del intercambio de información. Los resultados muestran que las cámaras de eco son determinantes importantes de los lazos de intercambio de información y que es probable que la influencia de la reputación "profundice" el eco. Los resultados también muestran que mientras más foros coparticipan un par de actores, es más probable que intercambien información. Esto se aplica al intercambio de información en general, así como al intercambio de información con socios de confianza. Los resultados indican que los foros permiten tanto el aprendizaje cognitivo (como ganancia de conocimiento) como el aprendizaje relacional (como relaciones mejoradas). No obstante, cuando las cámaras de eco son fuertes y muchos foros están polarizados, entonces la coparticipación del foro puede no dividir las cámaras de eco.